Debates contemporáneos en derecho de familias, de infancias y de adolescencias - Valencia Arias, Esneider Andrés; Ucrós Gámez, Mariana Stefany; Usma Cartagena, Manuela; Gómez Agudelo, Dany Steven; Mesa Elneser, Ana María; Aguirre Espinosa, Juan Esteban; Martínez Agudelo, Jomer Camilo; Arango Gallego, Luisa Fernanda; Mejía Alzate, Elmer Augusto; Gil Arcila, Natalia (Universidad Católica Luis Amigó, 2023)
This book is the result of the third call for papers entitled Contemporary Debates in Family Law, Childhood, and Adolescence, which has been held for three consecutive years due to the importance of this area for law and other related disciplines. Its purpose is to contribute to academic discussion from an interdisciplinary perspective. In this book, readers can approach current topics such as the best interests of the child; family law from a gender perspective; domestic violence; disability; and digital evidence and probative law.